Biodegradation of oil and grease from Agro-Food Industry by immobilised Serratia marcescens SA30 - Abdullah, Shakila; Mohd Nor, Farhah Husna; Khamidun, Mohd Hairul (Malaysian Analytical Sciences Society, 2021)
The agro-food industrial wastewater (AFIW) contains high concentrations of oils and grease (O&G), which are significant threats to aquatic environments. In the context of the removal of contaminants from wastewater, the capability of Serratia marcescens SA30 immobilized in a packed-bed column reactor (PBCR) of O&G removal from AFIW needs to be verified. This study analyses the Serratia marcescens SA30 immobilized on oil palm frond (OPF) in PBCR in order to elucidate its removal ability of O&G from AFIW. The physicochemical parameters of the AFIW samples collected from the agro-food industry were analyzed according to Standard Methods for Examination of Water and Wastewater. The PBCR treatment system was set up using immobilized Serratia marcescens SA30 onto OPF for the removal of O&G from AFIW. The AFIW samples were collected at the inlet and outlet of the PBCR, and the respective concentrations of O&G were determined. These values assert that the parameters does not comply the production limit set in Environmental Environment Quality B (Industrial Effluent Regulations, 2009). The performance of the PBCR realized 100% efficiency, with the population ranging from 108 – 107 with the immobilized Serratia marcescens SA30 acting as a biosurfactant-producing bacteria, which was achieved by experiments ran at a volumetric flow rate of 3 mL/min during treatment using concentrations of O&G at 100% v/v after 144 hours operation in the PBCR. The data obtained would provide a green and sustainable pathway for the removal of O&G from water.